Clinicopathologic changes associated with pasteurella multocoda B: 2 infection and its bacterial lipopolysaccharides and outer membrane protein in mice and calves - Abdullah, Faez Firdaus Jesse (2011)
Haemorrhagic septicaemia in cattle and buffaloes is an economically important livestock disease in Asia including Malaysia. This study was conducted to investigate the host cell responses towards Pasteurella multocida type B and its immunogens which are the lipopolysaccharides (LPS) and outer membrane protein (OMP) in mice and cattle. Two hundred healthy male mice of eight to ten weeks of age and eight clinically healthy, non-pregnant and non-lactating Brangus cross calves weighing 150 ± 50 kg were used in this study. Throughout the experiments, three types of inocula were used that consisted of live wild-type P. multocida B:2, the lipopolysaccharide (LPS) of P. multocida B:2 and the outer membrane proteins (OMP) of P. multocida B:2 . The two hundred mice were divided into four equal groups of 50 mice each and the calves were divided into 4 groups of 2 cows in each group. The control group 1 (mice and calves) were inoculated with sterile phosphate buffered saline (PBS) whereas group 2 were inoculated with live wild-type P. multocida and group 3 were inoculated with LPS broth extract. Animals (mice and calves) in group 4 was inoculated with OMP broth extract. All animals were observed for 48 hours (h) for clinical signs, changes in behavior and mortality pattern, including the time of death. Clinical scoring was done and the data was analysed using statistics. Blood samples were collected into plain, EDTA and sodium citrate containing tubes for blood and biochemistry analysis and acute phase protein analyses. Moribund animals were euthanized while the surviving animals were killed after 48 h. Post-mortem examination of gross lesions was conducted and lung, liver and heart samples were fixed for histopathology and cellular changes were scored and analysed using statistics. Mice and calves in all treated groups showed significant (p<0.05) changes in clinical signs compared to control group 1 with group 2 showed most severe clinical response. Mice and calves in all treated groups showed significant (p<0.05) increased in positive acute phase protein concentrations. Mice and calves in all treated groups showed significant (p<0.05) changes in blood and biochemistry parameters with differences in severity of changes. Mice and calves in all treated groups showed significant (p<0.05) cellular changes in the lung, liver and heart with different degree of severity of lesions. Therefore, from this study, it can be concluded that the mice and calves in the positive control group and LPS immunogen groups showed similar clinical responses. For OMP immunogen group, there were differences in the severity of clinical responses between mice and calves, where in mice severe clinical responses were exhibited. Mice and calves were able to show significant increased in positive APPs. Hp and SAA were sensitive APPs for both mice and calves for P. multocida type B infection and its immunogens. Mice and calves exhibited blood and biochemistry changes towards the immunogens. The cellular changes except for the prominence of kupffer cells in the three groups were similar in both mice and calves.